Anticancer therapy-induced vascular toxicity: VEGF inhibition and beyond. (15th January 2017) - Di Lisi, Daniela; Madonna, Rosalinda; Zito, Concetta; Bronte, Enrico; Badalamenti, Giuseppe; Parrella, Paolo; Monte, Ines; Tocchetti, Carlo Gabriele; Russo, Antonio; Novo, Giuseppina
Abstract: Cardiotoxicity induced by chemotherapeutic agents and radiotherapy is a growing problem. In recent years, an increasing number of new drugs with targeted action have been designed. These molecules, such as monoclonal antibodies and tyrosine kinase inhibitors, can cause different type of toxicities compared to traditional chemotherapy. However, they can also cause cardiac complications such as heart failure, arterial hypertension, QT interval prolongation and arrhythmias. Currently, a field of intense research is the vascular toxicity induced by new biologic drugs, particularly those which inhibit vascular endothelial growth factor (VEGF) and its receptor (VEGF-R) and other tyrosine kinases. In this review, we aim at focusing on the problem of vascular toxicity induced by new targeted therapies, chemotherapy and radiotherapy, and describe the main mechanisms and emphasizing the importance of early diagnosis of vascular damage, in order to prevent clinical complications. Highlights: Growing scientific interest has been focused on the problem of cardiac toxicity induced by antineoplastic drugs. Drugs that inhibit vascular endothelial growth factor (VEGF) and its receptor (VEGF-R) can also cause vascular damage. This paper aims to discuss the diagnostic tools available to precociously detect it.